Prenatal Diagnosis of Ebstein Anomaly in a Centre with Limited Resources: A Potential Pitfall - Bejiqi, Ramush; Retkoceri, Ragip; Bejiqi, Hana; Mustafa, Aferdita; Maloku, Arlinda; Bejiqi, Rinor (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Ebstein anomaly is a rare congenital cardiac malformation characterized by varying degrees of downward displacement of the tricuspid valve leaflets into the cavity of the right ventricle. The pathophysiology varies with the degree of valvular malfunction, the size, and contractility of the right ventricle, and the presence of obstruction within the right ventricular outflow tract. An early diagnosis makes worse the often prognosis. Fetal echocardiography is a useful tool for the diagnosis of congenital heart disease including the Ebstein anomaly which shows a wide spectrum of ultrasonographic manifestations and, sometimes it can be difficult to make a true prenatal diagnosis. CASE REPORT: Here, we describe a unique case of an Ebstein anomaly in 26 weeks of gestation fetus through prenatal echocardiographic evaluation. Fetus was suspected as a severe form of the Ebstein anomaly, with a severe form of right atrium enlargement, huge tricuspid insufficiency, and hypoplastic pulmonary artery. The atrial septum, dimensions of cardiac structures, left and right cardiac output, and Doppler interrogation of cardiac flows were examined. CONCLUSION: This case study presents a well-documented case of Ebstein’s anomaly type D that was diagnosed prenatally using fetal echocardiography.